Hubungan antara Tingkat Kedisiplinan Pemakaian Masker dengan Kapasitas Fungsi Paru Tenaga Kerja Terpapar Debu Kapas pada Bagian Winding di PT. Bintang Makmur Sentosa Tekstil Industri (BMSTI) Sragen - Indrianti, Leni (2016)
Cotton dust including organic dust containing carbon that are fibrosis of the lungs. The purpose of the study was to determine the relationship of the level of discipline the use of a mask with lung function capacity workers exposed to cotton dust in the winding PT. Bintang Makmur Sentosa Textile Industry Sragen. Analytic observational research with cross sectional study design purposive sampling. The total samples were 38 respondents. The file were analyzed using univariate and bivariate. The results of measurements of average levels of cotton dust in the winding section on 10 points is 7,975 mg /m^3 exceeded the allowed NAB is 0.2 mg/m^3. Data analysis used Spearman Rho . The study concluded there is a correlation between the level of discipline the use of a mask with lung function capacity obtained p-value 0.003 < 0.05 by the closeness of the relationship is quite strong ( r 0.471 ) which means that the level of the relationship is strong enough . It is recommended that labor discipline always wear masks to reduce the risk of pulmonary function